Pengaruh Strategi Pembina Ekstrakurikuler Kitab Kuning dalam Meningkatkan Prestasi Peserta Didik di Pesantren Musthafawiyah - Nadia Syahida Lbs; Ali Yusron; Ainun Mardia Harahap (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study aims to determine the influence of the yellow book extracurricular instructor strategy in improving student achievement. This study was conducted at the Musthafawiyah Islamic Boarding School. In this study, the researcher took samples using Total Sampling (saturated sample), this is because the population is less than 100 so that the entire population is used as a sample. The sample of this study was 48 people. The results of the data analysis obtained using data analysis techniques, namely descriptive analysis, requirement testing and hypothesis testing using the SPSS version 23 program. The results of the data analysis obtained the correlation coefficient value (rxy) = 0.536 with sig. (ρ) = 0.000 <0.05. So it can be concluded that Ho is rejected and Ha is accepted, with a coefficient of determination (R2) of 0.287 of 28.7% with the remaining percentage of 71.3% influenced by other variables. With Fcount of 18.524. The conclusion is that there is a significant influence between the extracurricular yellow book mentor strategy variables in improving student achievement at the Musthafawiyah Islamic Boarding School. The extracurricular mentor strategy (X) has a significant effect on improving student achievement (Y). with a determination coefficient (R2) of 0.287, which means that the extracurricular mentor strategy has an effect on improving student achievement with a percentage of 28.7% with the remaining percentage of 71.3% influenced by other variables. Student achievement (Y) at the Musthafawiyah Islamic boarding school has a significance value of 0.128> 0.05, so the data is declared normally distributed and is in the good category with a percentage of 87.2%.